Power, crime and criminology in the new imperial age - Michalowski, Raymond J. (Crime, law and social change, 2009)
As a consequence of the U.S. pursuit of neo-liberal global hegemony in the post-Soviet era, the language of empire has returned to political discourse and social analysis after an eighty-year absence. Although the pursuit of empire and the exertion of imperial control is deeply and demonstrably injurious to the nations and people subjected to this control, orthodox criminology has given relatively little attention to this emerging world of transnational social injury, choosing instead to continue its traditional focus on private crimes of greed, lust and rage. In this essay I detail how legal formalism, methodological individualism, ameliorative motives, mass-communications and the reward structure of orthodox criminology combine to form a meta-theoretical framework that has kept the criminological gaze averted from injurious actions of transnational structures of power. I then offer an alternative framework for a criminology of empire and other power crimes focused on how intersections among economic, political and cultural processes generate social injuries that are analogous to crimes in their nature and consequences, and that, as a result should become as significant a focus of criminological inquiry as the street crimes that now dominate criminological research and writing. *** What do we do with our knowledge about the suffering of others, and what does this knowledge do to us?***-Stanley Cohen